Social Representations of Daily Mobility: An Approach from Sustainability - Castro-Sánchez, Laura-Elena (2022)
In the context of growing global daily mobility, fragmented visions of knowledge predominate when assisting policies for advancing the sustainability of this phenomenon. Such visions have mostly focused on material aspects. In this paper, from an inter- and transdisciplinary perspective, a hybridization of theoretical perspectives around the notions of daily mobility and sustainability is proposed. For that, we review the existing literature to provide theoretical approaches and key concepts for the construction of a Sustainable Daily Mobility Index - IMCS. That index comprises a set of indicators around four dimensions: ecology, well-being, governance and culture; the latter seen from prevailing social representations and as a way forward to establish nexuses with the material dimension of daily mobility. Based on preliminary findings for the case of Barrio Antiguo in the city of Monterrey, Mexico, we conclude with a reflection on the IMCS usefulness in a Latin American context where socioeconomic, cultural and spatial characteristics turn social representations into a key explanatory factor of many mobility dynamics, challenges, and potential solutions.